Comparação do tabagismo com os níveis de atividade física, capacidade funcional e saúde cardiovascular em pacientes com doença arterial periférica - Rigoni, Vera Lucia Silva (2019)
Peripheral artery disease (PAD) is a chronic, progressive disease that generates stenosis of the vascular bed of extremities. Smoking is a frequent habit in these patients with symptomatic PAD. Objective: To compare smoking on levels of physical activity, functional capacity and cardiovascular health of smoker patients with symptomatic PAD. Methods: The sample included 180 patients with symptomatic PAD who met the following inclusion criteria: age greater than or equal to 40 years, grade 2 PAD in one or both of limbs identified by the ankle brachial index of less than 0.90, and symptoms of intermittent claudication. Patients were divided into the following three groups: smokers, ex-smokers and non-smokers. Smoking was defined by current consumption or during the prior six months of cigarette, cigar, pipe. Patients who had quit smoking for more than six months were considered as ex-smokers, and those who did not smoked were classified as non-smokers. In the three groups, were analyzed physical activity levels (accelerometry), functional capacity (6-minute walk test, muscle strength test and balance test) and cardiovascular health indicators (blood pressure, cardiac autonomic modulation and indicator of arterial stiffness). Results: The levels of physical activity, functional capacity, blood pressure and arterial stiffness were similar (p>0.05) among smokers, ex-smokers and non-smokers. Smokers had higher values in the HF band (64 ± 22nu) compared to ex-smokers (54 ± 20nu) and non-smokers (48 ± 18nu) (p=0.047). Smokers had lower values in the low band (LF) (36 ± 22nu) compared to ex-smokers (46 ± 20nu), and non-smokers (52 ± 18nu) (p<0.01). As a consequence, the vagal sympathetic effect balance (LF / HF) was higher in smokers (2.65 ± 1.93) compared to ex-smokers (1.71 ± 1.48) and non-smokers (1.27 ± 1.09) (p<0.01). Conclusion: In patients with symptomatic PAD, smoking is associated with lower autonomic vagal modulation sympathetic and greater sympathetic autonomic modulation. In contrast, smoking does not seem to affect levels of physical activity, functional capacity, blood pressure and arterial stiffness of the patients.